Method And Controller For Flexible Process Control - FRIEDRICH HACKL; CARSTEN KOLODZIEJ; FRIEDRICH WEGENER; ROBERT WILMES (2016)
To simplify and/or more flexibly implement a process control by means of a control device, a method is provided for process control in which at least one first and one second data processing module are executed by a control device during operation, wherein an operating program of the control device automatically implements an exchange of data between assigned data objects of the first and the second data processing module, and wherein the assignment between the data objects of the first and the second data processing modules is modified during operation of the control device in order to modify the process control. In addition, the control device is designed to carry out the method, as well as an operating program for such a control device, which can particularly be saved on a data storage device. 为了简化和/或灵活设计通过控制装置进行的过程控制，本发明涉及种用于过程控制的方法，其中由控制装置(100)在运行中运行至少个第和第二数据处理模块(210，220)，其中自动地由控制装置(100)的操作程序引起第和第二数据处理模块(210，22)的对应的数据对象之间的数据交换，并且其中在控制装置(100)的运行中改变第和第二数据处理模块(210，220)的数据对象之间的映射，以便促使过程控制改变。此外，本发明还涉及种构造用于实施该